Investigación sobre News Sharing. Una propuesta de análisis bibliométrico - Quevedo-Redondo, Raquel; Antona Jimeno, Tamara; Vicent-Ibáñez, Mireya (Communication&Society-Spain, 2022)
Esta investigación utiliza la bibliometría como herramienta para averiguar si la difusión de noticias en redes sociales conforma un campo de investigación maduro. Mediante la consulta de la base de datos Web of Science, a través de la búsqueda del término ‘news sharing’ en títulos, palabras clave y resúmenes, se obtiene un universo de 133 artículos que permiten enfrentar la pregunta sobre si existen revistas y autores consolidados. Los resultados obtenidos revelan cierta ambigüedad que explicaría por qué la temática escogida se estudia a menudo desde ámbitos ajenos a la comunicación, sin que la presencia heterogénea de investigadores se traduzca en una mayor interdisciplinariedad.
Research on News Sharing. A Proposal of bibliometric analysis
This study seeks to establish whether news sharing in social media is a mature field of research by using bibliometrics as a tool. The Web of Science database was searched for articles that contained the term 'news sharing' in titles, keywords, and abstracts. A total of 133 articles was obtained, which enabled us to address the question of whether there are well-established journals and authors that cover the subject. The results show a certain ambiguity, which could explain why the chosen subject matter is often studied in fields outside of Communication Studies; however, while studies on news sharing are conducted by researchers from heterogeneous fields, this has not translated into greater interdisciplinarity.
Keywords: news sharing; redes sociales; análisis bibliométrico; Web of Science; co-citación; social media; bibliometric analyses; co-citation; Emerging; Scopus